A comprehensive techno-economic assessment of a novel compressed air energy storage (CAES) integrated with geothermal and solar energy. (October 2021) - Mousavi, Shadi Bashiri; Ahmadi, Pouria; Pourahmadiyan, Ali; Hanafizadeh, Pedram
Abstract: Increasing the renewable energy share in most of the energy sectors is proven to be a vital option for most countries. Geothermal and solar energy have recently gained utmost attraction as green alternatives to replace fossil fuels. To take the most advantage of the renewable sources regarding their stochastic behavior, energy storage systems are employed for peak shaving and load leveling in power generation units. In this research, a novel configuration of a compressed air energy storage (CAES) integrated with Organic Rankin Cycle (ORC) which utilizes geothermal and solar energy as a green thermal source is designed, analyses and investigated. Energy, exergy, and exergoeconomic analyses are used as potential tools to observe and assess the performance of the designed system. To achieve a better understating of the effect of design parameters on the system performance, a parametric analysis is conducted. CAES inlet pressure and ORC operating pressure are chosen as decision variables to perform the multi-objective optimization using a genetic algorithm. Results show that the solar collector unit with a share of 47% is responsible for the highest exergy destruction rate in the system. Employing the proposed system at the design condition can produce 1314 kWh power for peak shaving and 0.3 kg/s hot water with 35.41% and 31.17% overall energy and exergy efficiency respectively. Besides, applying multi-objective optimization shows that at the optimum condition, the exergy efficiency and total cost rate of the system are 29% and 18 /h, respectively.